Media Education in Family: The Attitudes and Approaches of Czech Parents - Stastna, Lucie; Wolak, Radim; Cigankova, Klara (e-Pedagogium, 2014)
The article focuses on the topic of media education in family environment in the Czech Republic. The theoretical section of the text sums up how this topic was processed in foreign and Czech studies. It includes also the broader context of the topic. The practical part of the article summarizes results of two qualitative analysis of in-depth interviews with parents who have children between the ages of 12 and 15. The analysis aims to contribute to the knowledge of a) how parents perceive the relationship between their children and the media and b) how they cope with the role of "media educator".
Keywords: family; educational strategies; media literacy; family media education; parental mediation